Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd001973.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating oral mucositis for patients with cancer receiving treatment

Abstract: Analysis 1.1. Comparison 1 benzydamine mouthwash versus placebo, Outcome 1 Improvement in mucositis.. .. Analysis 2.1. Comparison 2 low level laser versus sham, Outcome 1 Mild to moderate mucositis.. .. .. .. Analysis 3.1. Comparison 3 sucralfate versus placebo/salt and water/salt and soda, Outcome 1 Mucostis eradicated.. Analysis 4.1. Comparison 4 morphine (PCA) versus morphine (CI), Outcome 1 Average pain score.. .. .. . Analysis 4.2. Comparison 4 morphine (PCA) versus morphine (CI), Outcome 2 Daily mean opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
0
25
0
5
Order By: Relevance
“…31,32 Povidone-Iodine (oral) Although earlier trials demonstrated significant reductions in onset, incidence, total duration, and worst grade of oral mucositis with oral povidone-iodine, 9,17,29 a more recent randomized controlled trial (N = 132) did not. Side effects of this agent include tachycardia and palpitations.…”
Section: Pilocarpinementioning
confidence: 99%
“…31,32 Povidone-Iodine (oral) Although earlier trials demonstrated significant reductions in onset, incidence, total duration, and worst grade of oral mucositis with oral povidone-iodine, 9,17,29 a more recent randomized controlled trial (N = 132) did not. Side effects of this agent include tachycardia and palpitations.…”
Section: Pilocarpinementioning
confidence: 99%
“…Als häufigste Schmerzursache während der antineo plastischen Therapie wird von betrof fenen Kindern, deren Eltern und Kinde ronkologen die therapiebedingte Muko sitis genannt [21,22,26,37]. Die chemo therapieassoziierte Mukositis tritt wäh rend bestimmter Behandlungsprotokolle regelmäßig und vorhersagbar auf [9]. Ih re Dauer und Schwere variieren von Pa tient zu Patient (in Abhängigkeit von den eingesetzten Chemotherapeutika, aber auch bei gleicher Behandlung) und durch unterschiedlich lange Pausen vor den Chemotherapiezyklen oder anderen Begleitumständen in geringerem Maße von Chemotherapiezyklus zu Chemo therapiezyklus beim gleichen Patienten [1,2].…”
Section: Zirkadianer Rhythmus Des Pca-gesteuerten Opioidverbrauchs Beunclassified
“…In den 3 verfügbaren pädiatrischen Stu dien erweist sich die PCA jedoch als ei [15,23]. Dies wird durch ei ne aktuelle CochraneAnalyse belegt und entspricht den Erkenntnissen zum opio idsparenden Effekt der PCA in der post operativen Schmerztherapie [9,20].…”
Section: Pca Zur Schmerztherapie Bei Mukositisunclassified
See 1 more Smart Citation
“…[5][6][7] Newer products: MuGard TM , Caphosol R and Episil R have been recently introduced. Given the radiotherapy treatment volume in SCCHN, the majority of the oral mucosa will receive a significant dose of radiation; OM is realistically an inevitable toxicity rather than preventable consequence of head and neck radiotherapy.…”
Section: Introductionmentioning
confidence: 99%